IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DALAM PEMBELAJARAN FIQIH KELAS VIII DI SMP NU BAITUSSALAM SIMBAR - Sari, Putri Ratna; Muttaqin, Ahmad Izza; Fauzi, Anis (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
The learning method is a technique used to achieve established goals. In teaching and learning activities, methods are essential for teachers to succeed in delivering lessons and achieving the desired objectives. This study uses a descriptive qualitative approach. Data collection techniques employed by the researcher include observation, interviews, and documentation, with purposive sampling used for selecting participants. Data analysis follows qualitative procedures, encompassing data reduction, data presentation, and drawing conclusions, with data validity ensured through triangulation. Field research results show that in implementing the Teams Games Tournament method, the teacher goes through several stages: planning, implementation, and evaluation. In the planning stage, the teacher prepares the syllabus, lesson plans, and learning materials. During implementation, the teacher presents core learning content, organizes students into groups, facilitates tournament games, and awards prizes. In the evaluation stage, the teacher assesses students across three aspects: cognitive, affective, and psychomotor. Supporting and inhibiting factors may stem from students, teachers, and situational aspects, as these elements impact the smoothness of the learning process in the classroom